Agrarian Storytellers: Pollen and Charred Plant Macrofossils of Ancient Field Layers - Eldegard Jensen, Christin (In Situ Archaeologica, 2020)
This paper offers a descriptive overview and main trends of pollen and macrofossil data obtained from 19 archaeological sites in Rogaland, SW Norway, excavated between 1998 and 2018. The dataset covers the period from late Neolithic until the Middle Ages. Pros and cons of the two botanical methods are discussed, concluding that there are clear advantages in joint application as there are significant differences in their statement value. Pollen and charred plant macrofossils function as complementary variables as they represent different biological stages of the same plant species, and because of differences in dispersal mechanisms and preservation in aerobic soils. The greater possibility to identify macrofossils of cereals and weeds to species and sub-species level is a strong advantage. By including pollen analysis, one achieves a higher total biodiversity, and by that the reflection of a wider environmental spectrum giving room for the inclusion of new issues in archaeological research.